The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/8096539
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Single-Rooted Mandibular Second Molar with Single Canal

Abstract: The root canal anatomy of mandibular second molar teeth is known to be highly variable. Whilst the most frequently seen configuration is two mesial canals and one distal canal, other variations such as four canals, two canals, and C-shaped canal system do also exist. This case report describes the diagnosis and management of unusual root canal configuration of a mandibular second molar, with one canal in a single conical root, using the contemporary advancements in endodontics. Following clinical and radiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…In single-rooted mandibular molars, the mesial canal configuration has been categorized into Vertucci types I, II, IV and V, while the distal root canal configuration is commonly reported to be Vertucci type I [ 7 ]. A previously published case report by Alfadley et al has demonstrated the rare occurrence of a Vertucci type I canal in a second molar in a Saudi Arabian population [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In single-rooted mandibular molars, the mesial canal configuration has been categorized into Vertucci types I, II, IV and V, while the distal root canal configuration is commonly reported to be Vertucci type I [ 7 ]. A previously published case report by Alfadley et al has demonstrated the rare occurrence of a Vertucci type I canal in a second molar in a Saudi Arabian population [ 8 ].…”
Section: Introductionmentioning
confidence: 99%